CALCULUS LEARNING VIA SCREENCAST-O-MATIC DURING THE PANDEMIC: AN EXPLORATION TOWARDS STUDENTS’ PERCEPTION OF MATH ANXIETY - Robert Harry Soesanto; Kurnia Putri Sepdikasari Dirgantoro (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
The emergence of the Covid-19 pandemic has transformed the learning system into an online mode, where students' anxiety became the spotlight for educators to create a learning environment that actively engages them. Many educators are competing in maximizing the use of technology to ensure students are engaged in the learning process. The study aims to explore students’ perception of math anxiety through the implementation of Screencast-O-Matic in calculus learning. This study involves 41 students at the university level and is conducted in mixed methods, using statistics and narrative descriptives. Questionnaires and open-ended questions are used to investigate students’ testimonies about the video made by Screencast-O-Matic and their perceptions of math anxiety after learning with the video given. The results showed that the implementation of Screencast-O-Matic video gradually reduces students’ mathematics anxiety during online calculus learning. Screencast-O-Matic offers educators the opportunity to build a web-based lecture learning system in audio-visual media to minimize students' anxiety levels. Furthermore, the most important things to consider while creating an educational video are clarity of message, user-friendliness, good visualization, and easy access to students anytime and anywhere.